Modern american drama Eugene O'Neil Long Day's journey into night - Lumet, Sidney; Landau, Ely (History of drama/ produced by Harold Mantell., 1976)
A broading, devastating film based on Eugene O'Neil's most powerful and autobiographical play, about a day in the life of a family deteriorating because of drug addiction, alcoholism and imminent death.